2010
DOI: 10.1177/145749691009900312
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Wound Infections after Vascular Surgery: Prospective Multicenter Observational Study

Abstract: Background and Aims: this multicenter prospective observational study defined the incidence and risk factors of surgical wound infections (Swi) after infrarenal aortic and lower limb vascular surgery procedures and evaluated the severity and costs of these infections.Methods: the study cohort comprised of 184 consecutive patients. postoperative complications were recorded. the additional costs attributable to Swi were calculated.Results: eighty-four (46%) patients had critical ischaemia, 81 (45%) patients unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
84
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(90 citation statements)
references
References 19 publications
2
84
0
4
Order By: Relevance
“…It has been suggested that the true prevalence of SSI is underestimated, depending on surgical specialty, accepted and validated definitions and the comprehensiveness of postoperative surveillance [8][9] . When close post-discharge surveillance is included, particularly with the involvement of unbiased, trained and validated observers, SSIs have been reported to complicate 10-20% of surgical operations indicating that there is widespread underestimation of SSI rates across all classes of surgery [10][11][12][13][14][15][16][17][18] .…”
Section: Introduction Epidemiology and Costs Of Ssismentioning
confidence: 99%
“…It has been suggested that the true prevalence of SSI is underestimated, depending on surgical specialty, accepted and validated definitions and the comprehensiveness of postoperative surveillance [8][9] . When close post-discharge surveillance is included, particularly with the involvement of unbiased, trained and validated observers, SSIs have been reported to complicate 10-20% of surgical operations indicating that there is widespread underestimation of SSI rates across all classes of surgery [10][11][12][13][14][15][16][17][18] .…”
Section: Introduction Epidemiology and Costs Of Ssismentioning
confidence: 99%
“…[10][11][12] Çalışmamızdaki tüm olguların enfeksiyon kaynağı hakkında tam bir bilgiye sahip değiliz. Çünkü bu 13 olguluk seride kliniğimizde yapılan operasyon sonrası enfeksiyon gelişen olgu sayısı yalnızca üçtür.…”
Section: Discussionunclassified
“…7 Port site infection is a persistent problem for patients with an adjustable gastric band, despite perioperative antibiotics and application of standard measures of antisepsis before, during and after surgery. Obesity is associated with a greater chance of wound infection, 8 and the insertion of foreign material, such as an injection port, provides a nidus for the infection. Whereas wound infection is a major impediment for the patient, it has not been a life-threatening complication; in all but 2 patients the infections were treated using local measures.…”
Section: Discussionmentioning
confidence: 99%